PERANCANGAN IDENTITAS VISUAL LAYANAN MOBILE GROOMING HI PETS - Jemima Katherine Lemuela; Edy Chandra (Gorga : Jurnal Seni Rupa, 2023)
Hi Pets was founded in 2020, selling dog and cat equipment. hi pets is also a provider of grooming services. hi pets already has a physical store in the kelapa gading area, north jakarta. in the last 2 years the pet shop business has grown rapidly, thereby increasing competition. this is the background behind the owner of hi pets to create a new business unit, namely mobile grooming services. with this new service, a visual identity is needed that can represent the value of the service. this design was made with the aim of producing a visual identity design for mobile grooming services that displays the value of the service, as well as the application of visual identity in supporting media. the methods used in this design are problem identification, data collection, data analysis, research, creative process, and design execution. in addition, qualitative methods are also used which aim to obtain descriptive and in-depth data. and supported by an analysis of strengths and weaknesses to find out the right strategy to use in this design. the results of designing this visual identity are in the form of a logo, as well as its application in various media in the form of car boxes / van grooming, staff uniforms, apron groomers, name cards, stationery sets, price list designs, invoice designs, loyalty cards, social media content, mini websites, grooming equipment and merchandise.Keywords: mobile grooming, design, visual identity. AbstrakHi Pets berdiri pada tahun 2020, dengan menjual perlengkapan anjing dan kucing. Hi Pets juga merupakan penyedia jasa layanan grooming. Hi Pets telah memiliki toko fisik di Kawasan Kelapa Gading, Jakarta Utara. Dalam 2 tahun terakhir bisnis usaha pet shop berkembang pesat, sehingga meningkatkan persaingan. Hal ini lah yang melatarbelakangi owner dari Hi Pets untuk membuat unit bisnis baru yaitu layanan mobile grooming. Dengan adanya layanan baru tersebut maka diperlukan sebuah identitas visual yang dapat merepresentasikan value layanan tersebut. Perancangan ini dibuat bertujuan untuk menghasilkan rancangan identitas visual layanan mobile grooming yang menampilkan value dari layanan tersebut, serta pengaplikasian identitas visual pada media pendukung. Metode yang digunakan dalam perancangan ini adalah identifikasi masalah, pengumpulan data, analisis data, riset, proses kreatif, dan ekesekusi perancangan desain. Selain itu digunakan juga metode kualitatif yang bertujuan untuk mendapatkan data yang bersifat deskriptif dan mendalam. Serta didukung dengan analisis kelebihan dan kekurangan untuk mengetahui strategi yang tepat untuk digunakan dalam perancangan ini. Hasil dari perancangan identitas visual ini berupa logo, serta pengaplikasiannya di berbagai media berupa Mobil Box / Van Grooming, Seragam staff, Apron groomer, Kartu Nama, Stationery Set, Desain Daftar Harga, Desain Invoice, Loyalty Card, Konten Sosial Media, Mini Website, Peralatan grooming, dan Merchandise.Kata Kunci: mobile grooming, desain, identitas visual. Authors:Jemima Katherine Lemuela : Universitas TarumanagaraEdy Chandra : Universitas Tarumanagara References: Cornellin, E., & Paramita, S. (2019). Komunikasi Pemasaran Brand Lokal Kepada Masyarakat Indonesia (Studi Terhadap Beras Sikoki). Prologia, 3(1), 86“98.Darmawanto, E. (2019). Desain Komunikasi Visual II Perancangan Identitas Visual. Unisnu Press.Hanum, A., Azani, B., Purnomo, E., & Zaim, R. A. (2022). Perancangan Kemasan Rakik Mak Nis. Gorga: Jurnal Seni Rupa, 11(2), 286“379.Karsono, K., Purwanto, P., & Salman, A. M. Bin. (2021). Strategi Branding Dalam Meningkatkan Kepercayaan Masyarakat Terhadap Madrasah Tsanawiyah Negeri. Jurnal Ilmiah Ekonomi Islam, 7(2), 869“880.Landa, R. (2018). Graphic Design Solutions. Cengage Learning.Press, E. (2009). Start Your Own Pet Business and More: Pet Sitting, Dog Walking, Training, Grooming, Food/treats, Upscale Pet Products. Entrepreneur Press.Putra, R. W. (2021). Pengantar Desain Komunikasi Visual dalam Penerapan. Penerbit Andi.Rustan, S. (2021). LOGO 2021. Jakarta: Nulis Buku Jendela Dunia.Sari, D. M., Fitryona, N., & Sandra, Y. (2022). Konsep Kreatif Desain Ikon Bangunan Peta Shelter Mitigasi Universitas Negeri Padang. Gorga: Jurnal Seni Rupa, 11(2), 355“360.Soleh, O., Wuryani, R., & Farizi, R. (2017). OPet™s is Petshop Mobile Application to Meet All The Needs of Pets (Day-Care, Shopping And Grooming): Development And Business. 2017 2nd International Conferences on Information Technology, Information Systems and Electrical Engineering (ICITISEE), 141“146.Wispandono, M. (2012). Penciptaan Entrepreneur Kompetitif Melalui Pengoptimalan Otak Kanan (Studi Kasus Pada Mahasiswa UTM). Prosiding Seminas Competitive Advantage, 1(2).Wrona, K. (2015). Visual Identity and Rebranding. Marketing of Scientific and Research Organizations, 16(2), 91“119.